The effects of teaching critical thinking on studentsâ argumentative essay - Khunaifi, AÃ¢Â€Â™am Rifaldi (Journal on English as a Foreign Language (JEFL), 2015)
This study is directed to find out whether teaching critical thinking affects the writing ability of argumentative essay. This research employed quasi experimental design as it was intended to measure the effects of the strategy on the studentsâ ability in writing argumentative essay. The samples of the study were the students of class A and B enrolled in the seventh semester of the English Education Department of State Islamic College of Palangka Raya. To collect the data needed, it was used test as the instrument; it was Academic Writing for IELTS Test. The data were processed and analyzed by using SPSS 19.0 statistic technique of independent t-test and paired-sample t-test, and the analized data were concluded. From the result of the test, the independent t-test calculation in posttest scores in both groups shows that the significance value is higher than level of significance (0.194 > 0.05). It indicates that there is no significant difference between experimental and control groups. Moreover, the paired t-test calculation shows the result of paired sample test (0.000 < 0.05) in which there is a significant difference between pretest and posttest scores in experimental group after having treatments.